Website Based Student Absence Application Design Using Extreme Programming Method: Study at a University in Bandung - Mochamad Jejen Jaelani; Soecipto Soecipto; Yenni Fatman; Siti Nur (LPPM STMIK Mardira Indonesia, 2023)
Absenteeism application is one of the systems where attendance is critical data in every activity, be it lecture activities. Nevertheless, often, the data - this absence of data is less noticed. The proof is that many educational institutions still use conventional absenteeism. Conditions like this are certainly very vulnerable to fraud. Therefore, the Informatics Engineering Study Program of the Faculty of Engineering needs a system that can create an absence process that can produce information more efficiently and by its standards, of course, using methods that can solve the problems in the Informatics Engineering Study Program of the Faculty of Engineering—using the Extreme Programming Method. The extreme Programming method was chosen because the software to be created is simple and classified as small-scale software, and development takes little time. This system development method is one of the agile methods. Which has several stages, namely: 1. Planning, 2. Design, 3. Coding, and 4. Testing. Of course, with some design processes that use UML, such as Use Case Diagram, Activity Diagram, Flowchart &, and DFD, the student attendance website application built has been tested for eligibility using Blackbox testing. The results of this study create a system that can help informatics engineering programs to help in terms of student retirement. Design a system that can produce reports that suit needs effectively and efficiently.